El concepto de nación entre la desintegración del virreinato del Nuevo Reino de Granada y la emergencia de la república de Colombia (Debates) - Rodríguez, Jaime Alberto (2022)
The article rebuilds the semantic web around the concept of nation. To this end it takes into account three important factors: first, events and their impacts on decisions made by stakeholders; second, political language and ideas (as markers of processes and factors of transformation); and finally, cultural components, especially territorial identities. This essay highlights the complexity that researchers must tackle when rebuilding a given semantic web, because both structural and contextual elements must be combined.